Dietary Intake Is Associated with Occlusal Force Rather Than Number of Teeth in 80-y-Old Japanese. (April 2017) - Inomata, C.; Ikebe, K.; Okubo, H.; Takeshita, H.; Mihara, Y.; Hatta, K.; Tada, S.; Enoki, K.; Ogawa, T.; Matsuda, K.; Gondo, Y.; Masui, Y.; et al.
There has been a growing interest in the association between the number of teeth and dietary intake in older populations. However, people around the age of 80 y have frequently lost most of their teeth, and dental prostheses replacing the missing teeth play an important role in masticatory function. Therefore, masticatory function cannot be evaluated by the number of teeth alone. The occlusal force of the complete dental arches is an index of masticatory function, reflecting not only the number of teeth, but the effect of removable dentures. The purpose of this cross-sectional study was to determine the relative importance of the number of teeth and occlusal force in association with dietary intake in 80-y-old Japanese people. This study included 760 community-dwelling Japanese people aged 79 y to 81 y. The authors measured bilateral maximal occlusal force in the intercuspal position using pressure-sensitive sheets. Removable denture wearers kept their dentures in place during the measurements. Energy-adjusted food groups and nutrient intake during the preceding month were assessed by a brief self-administered diet history questionnaire. The authors assessed linear trends in food and nutrient intake in relation to the number of teeth and occlusal force after adjusting for gender and socioeconomic status (education level, financial status, family structure, resident area and BMI). P values of < 0.05 were considered to be statistically significant. The authors found that the number of teeth was not associated with the energy-adjusted intake of any food group examined. In contrast, a decline in occlusal force was significantly associated with a lower intake of vegetables, fish and shellfish, protein, polyunsaturated fatty acids, dietary fiber and most vitamins and minerals ( P for trend < 0.05). We conclude that food and nutrient intake was more closely associated with occlusal force than the number of teeth in community-dwelling Japanese people aged 79 y to 81 y. Knowledge Transfer Statement: This cross-sectional study of older Japanese people showed that, after controlling for considerable covariates, occlusal force rather than the number of teeth is positively associated with energy-adjusted intake of vegetables, fish and shellfish, protein, polyunsaturated fatty acids, dietary fiber and most of vitamins and minerals. This means that reduced occlusal force may unconsciously lead older people toward a habitual unhealthy dietary intake. Older people have frequently lost most of their teeth and require prosthetics to restore masticatory function. Bilateral occlusal force is therefore a better measure of masticatory function than the number of remaining teeth. Our findings suggest that prosthetic rehabilitation is a significant factor in the prevention and management of chronic diseases and frailty through better dietary intake in older populations.